(untitled) - Iklim Consult SDN. BHD. (Sabah, Japan, 1999)
University Malaysia Sabah (UMS) is planning to introduce a post graduate program on Biodiversity Management. The proposed program is being introduced by UMS in collaboration with a consortium of Danish university.
Keywords: Conservation projects,Economic development projects,Ecosystem management,Dự án bảo tồn,Quản lý hệ sinh thái,Dự án phát triển kinh tế; Citizen participation,Công dân tham gia; Malaysia